Bioenergi sebagai Solusi Pembangunan Berkelanjutan di Lamongan Pantura: Sinergi Kebijakan, dan Pemberdayaan Masyarakat melalui Porter’s Five Forces Analysis - Tri Bagus Prabowo; Milla Viendyasari; Luky A Yusgiantoro (Journal of Empowerment Community, 2026)
The potential of bioenergy in the northern coastal region of Lamongan offers significant opportunities to support sustainable development through the utilization of abundant local natural resources. The development of bioenergy in this area depends heavily on the availability of raw materials, applied technology, and supportive government policies. This paper aims to analyze the factors influencing the competitiveness of the bioenergy industry in Lamongan using Porter’s Five Forces model. The analysis finds that the threat of new entrants is relatively low due to high investment barriers (about 30–40% of total initial costs) and limited technological capacity. However, policy incentives for renewable energy and market access could reduce these barriers within the next 5–10 years, in line with the National Electricity Supply Plan (RUPTL) 2021– 2030 targeting a 23% renewable energy share by 2025. Buyer power is strong, driven by a 15% annual increase in renewable energy demand, while supplier dependence on agricultural and fishery biomass creates production instability. Although substitute energy sources such as solar and wind present challenges, limited competition and growing policy support provide strategic opportunities. Strengthening cross-sector collaboration, innovation, and technological investment is essential to enhance Lamongan’s bioenergy competitiveness and contribution to SDG 7 and SDG 13.